â€œKenabianâ€ dalam Tradisi Islam dan Rekam Jejak serta Penuturannya - Prakosa, JB. Heru (Jurnal Orientasi Baru, 2013)
In Islamic tradition, Muhammad is believed to be a prophet; and his prophethood was proved with a miracle in the form of i’jaz al-Qur’an. This means that anyone was challenged to bring something like the Qur’an at the level of its eloquence, and yet no one was able to do it. The prophethood of Muhammad was then transmitted from one generation to another generation by his followers, through the Islamic history, from the 2nd till the 4th or 5th centuries of the Hijriah. The report of the words and deeds of the Prophet Muhammad is called hadith. Two main components of a hadith are the chain of transmitters (sanad) and the content or material of the hadith (matn). In fact, the study of hadith criticism should pay attention to those two components in balance. Apart from it, the study of hadith can also provide a room for building an interreligious encounter, both in theological and spiritual senses.